2021
DOI: 10.1007/s11412-021-09347-5
|View full text |Cite
|
Sign up to set email alerts
|

Guidance in computer-supported collaborative inquiry learning: Capturing aspects of affect and teacher support in science classrooms

Abstract: Technology-enhanced collaborative inquiry learning has gained a firm position in curricula across disciplines and educational settings and has become particularly pervasive in science classrooms. However, understanding of the teacher’s role in this context is limited. This study addresses the real-time shifts in focus and distribution of teachers’ guidance and support of different student groups during in-person computer-supported collaborative inquiry learning in science classrooms. Teachers’ self-perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…On the one hand, in recent years, computer-supported collaborative learning has mainly focused on inquiry learning, self-regulation learning, and learning analysis. For example, Pietarinen et al (2021) addressed the real-time shifts in focus and distribution of teachers’ guidance and support of different student groups during in-person computer-supported collaborative inquiry learning in science classrooms. The study concluded that it was discovered that the prior science competency of groups had no influence on teacher supervision and support; rather, instructors guided the groups they regarded to be motivated and eager to collaborate, according to the findings.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, in recent years, computer-supported collaborative learning has mainly focused on inquiry learning, self-regulation learning, and learning analysis. For example, Pietarinen et al (2021) addressed the real-time shifts in focus and distribution of teachers’ guidance and support of different student groups during in-person computer-supported collaborative inquiry learning in science classrooms. The study concluded that it was discovered that the prior science competency of groups had no influence on teacher supervision and support; rather, instructors guided the groups they regarded to be motivated and eager to collaborate, according to the findings.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, in recent years, computer-supported collaborative learning has mainly focused on inquiry learning, self-regulation learning, and learning analysis. For example, Pietarinen (2021) addressed the real-time shifts in focus and distribution of teachers' guid-ance and support of different student groups during in-person computer-supported collaborative inquiry learning in science classrooms [90]. The study concluded that it was discovered that the prior science competency of groups had no influence on teacher supervision and support; rather, instructors guided the groups they regarded to be motivated and eager to collaborate, according to the findings.…”
Section: Popular Topics and Emerging Trendsmentioning
confidence: 99%
“…These changes to classic teaching methods have also introduced new challenges as large classrooms, restructured as several small discussion groups, demand the attention of the teacher and the teaching assistants (Moust and Schmidt, 1994). Furthermore, it was shown that half of the teachers had difficulties understanding when their guidance was needed (Pietarinen et al, 2021).…”
Section: Mainmentioning
confidence: 99%